2021
DOI: 10.1096/fj.202101096r
|View full text |Cite
|
Sign up to set email alerts
|

Fusion and beyond: Satellite cell contributions to loading‐induced skeletal muscle adaptation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 236 publications
0
46
0
Order By: Relevance
“…Myonuclear accretion facilitates myofiber hypertrophy during development ( Moss and Leblond, 1971 ; White et al, 2010 ; Bachman et al, 2018 ; Cramer et al, 2020 ) and after resistance exercise ( Egner et al, 2016 ; Goh and Millay, 2017 ; Murach et al, 2021 ). To explore the extent to which myonuclear accretion facilitates regenerating myofiber hypertrophy after injury, we performed correlational analyses using myonuclear number and myofiber volume (mm 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myonuclear accretion facilitates myofiber hypertrophy during development ( Moss and Leblond, 1971 ; White et al, 2010 ; Bachman et al, 2018 ; Cramer et al, 2020 ) and after resistance exercise ( Egner et al, 2016 ; Goh and Millay, 2017 ; Murach et al, 2021 ). To explore the extent to which myonuclear accretion facilitates regenerating myofiber hypertrophy after injury, we performed correlational analyses using myonuclear number and myofiber volume (mm 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Myonuclear accretion occurs during postnatal development ( Moss and Leblond, 1971 ; White et al, 2010 ; Bachman et al, 2018 ; Cramer et al, 2020 ) and after resistance exercise training ( Egner et al, 2016 ; Goh and Millay, 2017 ; Murach et al, 2021 ). In both cases, myonuclei appear to be added to existing myofibers and positioned in a peripheral location.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of SCs in skeletal muscle hypertrophic growth has been highly debated and one factor that could explain the discrepancies toward the necessity of new myonuclei accretion is the age of the mice, as young mice (less than 4 months old) and not mature mice (more that 4 months old) require SC fusion to support myofiber hypertrophy ( Murach et al., 2017 , 2021a ). Because age dependence was not the main focus of this study, we pointed our attention on 2- to 3-month-old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Given their role as the sole source of myonuclei, satellite cells are also involved in the hypertrophic response to exercise (Murach et al . 2021 a ). Studies using satellite cell‐depleted mice have shown that some hypertrophy can be achieved without satellite cells, but in order to maximize the response to long‐term training, satellite cells are required (Englund et al .…”
Section: Introductionmentioning
confidence: 99%
“…Satellite cells are indispensable during embryonic myogenesis and for muscle regeneration during adulthood (Engquist & Zammit, 2021), due to their ability to proliferate, fuse and form myotubes. Given their role as the sole source of myonuclei, satellite cells are also involved in the hypertrophic response to exercise (Murach et al 2021a). Studies using satellite cell-depleted mice have shown that some hypertrophy can be achieved without satellite cells, but in order to maximize the response to long-term training, satellite cells are required (Englund et al 2020).…”
Section: Introductionmentioning
confidence: 99%